Home boy - Hansen, Joyce 1942- (New York Clarion Books, 1982)
As he seeks a place to hide, Marcus, a boy from the Islands now living in the Bronx, tries to figure out how he became involved in the stabbing of a fellow student.
Keywords: Bronx (New York, N.Y.) -- Fiction